2016
DOI: 10.1111/jcmm.13023
|View full text |Cite
|
Sign up to set email alerts
|

Reduced angiogenic gene expression in morbillivirus‐triggered oncolysis in a translational model for histiocytic sarcoma

Abstract: Histiocytic sarcoma represents a rare malignant tumour with a short survival time, indicating the need of novel treatment strategies including oncolytic virotherapy. The underlying molecular mechanisms of viral oncolysis are largely unknown. As cancer in companion animals shares striking similarities with human counterparts, we chose a permanent canine histiocytic sarcoma cell line (DH82 cells) to identify global transcriptome changes following infection with canine distemper virus (CDV), a paramyxovirus close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…Canine distemper virus represents a Morbillivirus closely related to human measles virus [9], with the latter already described as a promising oncolytic virus in human medicine that has reached the phase of clinical trials [10]. Similarly, the attenuated Onderstepoort vaccine strain of canine distemper virus (CDV-Ond) represents a potential oncolytic virus for the treatment of canine histiocytic sarcomas [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Canine distemper virus represents a Morbillivirus closely related to human measles virus [9], with the latter already described as a promising oncolytic virus in human medicine that has reached the phase of clinical trials [10]. Similarly, the attenuated Onderstepoort vaccine strain of canine distemper virus (CDV-Ond) represents a potential oncolytic virus for the treatment of canine histiocytic sarcomas [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously studies have reported that CDV induces apoptosis in many cancer cell lines, including canine neoplastic lymphocytes, canine adenofibrosarcoma cells, human breast cancer cells and human cervical cancer cells . Persistent infection by CDV exhibited anti‐angiogenic properties in a canine histiocytic cell line . These capacities suggest that it may find a practical use in oncolytic gene therapy .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Persistent infection by CDV exhibited anti-angiogenic properties in a canine histiocytic cell line. 19 These capacities suggest that it may find a practical use in oncolytic gene therapy. 20 However, compared to oncolytic MV, the oncolytic potential of CDV in canine mammary carcinoma (CMC) has received only limited attention and the underlying oncolytic mechanisms of CDV remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are few reports about the effects of oncolytic viruses (morbillivirus and ECHO‐7 virus) on canine and human histiocytic sarcoma . Therefore, data on the oncolytic effects of reovirus on histiocytic sarcoma cells are expected to serve as important evidences for the rational use of oncolytic viruses in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are few reports about the effects of oncolytic viruses (morbillivirus and ECHO-7 virus) on canine and human histiocytic sarcoma. [17][18][19] Therefore, data on the oncolytic effects of reovirus on histiocytic sarcoma cells are expected to serve as important evidences for the rational use of oncolytic viruses in clinical trials. In the present study, we examined the oncolytic effects, both in vitro and in vivo, of reovirus on canine histiocytic sarcoma cell lines and on normal DCs derived from healthy dogs.…”
mentioning
confidence: 99%